Modelling of shattered pellet injection experiments on the ASDEX Upgrade tokamak - Ansh Patel; A. Matsuyama; G. Papp; M. Lehnen; J. Artola; S. Jachmich; E. Fable; A. Bock; B. Kurzan; M. Hoelzl; W. Tang; M. Dunne; et al. (Nuclear Fusion)
In a shattered pellet injection (SPI) system the penetration and assimilation of the injected material depends on the speed and size distribution of the SPI fragments. ASDEX Upgrade (AUG) was recently equipped with a flexible SPI to study the effect of these parameters on disruption mitigation efficiency. In this paper we study the impact of different parameters on SPI assimilation with the 1.5D INDEX code. Scans of fragment sizes, speeds and different pellet compositions are carried out for single SPI into AUG H-mode plasmas. We use a semi-empirical global reconnection event (GRE) onset condition to study the material assimilation trends. For mixed deuterium-neon pellets, smaller/faster fragments start to assimilate quicker. However, at the expected onset of the GRE, larger/faster fragments end up assimilating more material. Variations in the injected neon content lead to a large difference in the assimilated neon for neon content below ${\lt}10^{21}$ atoms. For larger injected neon content, a self-regulating mechanism limits the variation in the amount of assimilated neon. We use a back-averaging model to simulate the plasmoid drift during pure deuterium injections with the back-averaging parameter determined by a interpretative simulation of an experimental pure deuterium injection discharge. Again, larger and faster fragments are found to lead to higher assimilation with the material assimilation limited to the plasma edge in general, due to the plasmoid drift. The trends of assimilation for varying fragment sizes, speeds and pellet composition qualitatively agree with the previously reported experimental observations.